Snake envenomation in veterinary medicine: comparative insights and emerging therapies - Migliorisi, Alessandro; Johnson, Tyler; Nelson, Tatum; Elane, George L.; Ueda, Yu; Hobbs, Kallie J. (Frontiers in Veterinary Science, 2026)
Snakebite envenomation poses a significant threat to both public health and animal welfare, resulting in substantial human suffering and economic burden worldwide. Recognized by the World Health Organization as a neglected tropical disease, snakebites disproportionately affect impoverished rural regions across Africa, Asia, and South America, with an estimated 2.7 million envenomations and 81,000–138,000 deaths annually. In veterinary medicine, snakebites are similarly impactful, with up to 300,000 animals affected each year in the United States alone—primarily dogs and cats—while global veterinary cases likely number in the millions. Despite this, snakebites remain non-notifiable diseases, contributing to significant underreporting. The economic implications are profound, with treatment costs for human victims exceeding $200,000 per case and veterinary care ranging from $8,000 to $50,000 per case, often surpassing the financial capacity of pet owners. Beyond acute care, long-term sequelae such as chronic neuropathy and tissue damage further compound the burden. Current literature is limited in comparative analyses of envenomation mechanisms across species, particularly in livestock. This review will create a deeper understanding of pathophysiology, treatment modalities, and emerging therapies. Understanding of this background is essential to further advancements in science surrounding snake envenomation in both human and veterinary species.